Aquisicão das fricativas interdentais do inglês: uma abordagem via restrições - Leitão, Emilia Lorentz de Carvalho (2007)
In this thesis English interdental fricative acquisition by Brazilians second language learners has been investigated. Data from oral productions of three students groups has been gathered. The first group is composed by sixth semester undergraduate students of UNIFRA English course. The second and third groups are composed by third and tenth semester students of an extra curricular English course of UFSC. First, a phonetic transcription of selected words that contained interdental fricatives has been performed. Then, an analysis based on Connectionist Optimality Theory proposed by BONILHA (2004) has been carried out. This analysis uses the reranking of constraints, and it reveals that Brazilians second language learners are prone to make substitutions of the segment /θ/ by the segment [t] as well as the substitutions of the segment /ð/ by the segment [d]. Furthermore, there is a strong impact of the Lexical Frequency on the learners behavior.